High-efficiency and durable V–Ti–Nb ternary catalyst prepared by a wet-solid mechanochemical method for sustainably producing acrylic acid via acetic acid–formaldehyde condensation. Issue 3 (6th January 2023) - Liu, Jun; Yan, Youjun; Lian, Meng; Song, Jimei; Yang, Yongqi; Huang, Guofu; Wang, Miao; Feng, Xinzhen; Ji, Weijie
Abstract : High-efficiency and durable V–Ti–Nb ternary catalyst prepared by a wet-solid mechanochemical method to enhance efficient condensation of HAc/HCHO to AA/MA. Abstract : Based on the precise phase control V species adjustment of vanadium phosphorus oxides (VPOs), a series of metal oxides (Nb2 O5, MoO3, WO3, and Bi2 O3 ) were selected as modification agents to further enhance the catalytic activity and retain the excellent durability of VPO–TiO2 -based catalysts for the new procedure of producing acrylic acid via acetic acid–formaldehyde condensation. At an elevated liquid hourly space velocity (LHSV), the (AA + MA) selectivity reached 92.3% with a (MA + AA) formation rate of 63.8 μmol −1 gcat −1 min −1 over the Nb-decorated catalyst (catalyst VTi–Nb), and it maintained good durability for up to 100 h. The detailed characterization results of XRD, Raman, XPS, NH3 -TPD, CO2 -TPD, and H2 -TPR, demonstrated that the addition of Nb2 O5 could observably enhance the catalytic efficiency of the VPO–TiO2 catalyst. It not only improved the catalyst durability by enhancing prereduction of the V 5+ species, but also enhanced the active site density to improve the catalytic activity.